Toleransi Kedelai terhadap Tanah Salin - , Sunarto (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2001)
Saline soil is widely distributed in Indonesia. This soil could inhibit and reduce growth and production. The aims of this research was to know the responce of several soybean varieties and lines to salinity. The result of this research showed that line name T22 was susceptible to saline soil. Mlg 2510 line was very tolerant to saline soil, and on 0.4% salt concentration this line still produced seed.; Key words: Soybean, Saline soil.